Hanstruepera marina sp. nov. and Hanstruepera flava sp. nov., two novel species in the family Flavobacteriaceae isolated by a modified in situ cultivation technique from marine sediment - Ding, Hong; Liu, Jiahui; Yang, Chen; Guo, Chaobo; Ding, Lijian; Jung, Dawoon; Zhang, Weiyan (Frontiers in Microbiology, 2022)
A modified in situ cultivation technique was developed and applied to resource mining of uncultured microbes from marine sediments of Meishan Island in East China Sea. Two novel strains NBU2968T and NBU2984T were isolated by this method but not standard Petri dish, which indicated the modified technique was more effective compared to conventional approaches for isolating uncultured microbes and could be popularized and applied to other aquatic environments. The two novel strains were identified by polyphasic taxonomic approach. Cells of both strains were observed to be Gram-staining-negative, rod-shaped, non-motile, aerobic and yellow-pigmented. Catalase and oxidase activities, hydrolysis of Tweens 40, 60 and 80 of two novel strains were positive. Methyl red reaction, H2S production and hydrolysis of Tween 20 were negative. According to 16S rRNA gene sequence analysis, two novel strains shared highest similarities (96.4-97.7%) to the species with validated name in genus Hanstruepera, while shared lower sequence similarities (<95.6%) to all other genera. Phylogenetic analysis revealed that strains NBU2968T and NBU2984T were affiliated to the genus Hanstruepera. ANI and dDDH values between the two novel strains and Hanstruepera species were 77.4-78.3% and 20.4-20.9%, respectively, which below the thresholds for species delineation. The 16S rRNA gene sequence similarity, ANI and dDDH values between two novel strains was 99.3%, 88.9% and 36.3%, respectively, indicating that the two strains represent different species. The genomes of NBU2968T and NBU2984T were 3.28 Mbp with G+C content 34.2% and 3.09 Mbp with G+C content 34.4%, respectively. The only respiratory quinone was menaquinone-6 (MK-6). The major cellular fatty acids were iso-C15:0, iso-C15:1G and iso-C17:0 3-OH. The major polar lipids of the two strains were phosphatidylethanolamine, unidentified aminolipids and unidentified lipids. Based on the above polyphasic characteristics, strains NBU2968T and NBU2984T represent two novel species within the genus Hanstruepera, for which the names Hanstruepera marina sp. nov. and Hanstruepera flava sp. nov. are proposed. The type strains are NBU2968T (=MCCC 1K06392T=KCTC 82913T) and NBU2984T (=MCCC 1K07472T), respectively.